RETRACTED : Analysis of Financial Performance of Tegal Regency Local Government - Eka Nova; Supriyadi; Kumba Digdowiseiso (Journal of Social Science)
The management and accountability in the activities of regional autonomy and local finance are regulated by Government Regulation Number 1 of 2022, which states that financial management at the regional level starts from the initial planning to the supervision of the regional finances. The success of performance improvement is deemed effective when it aligns with government regulations. Kabupaten Tegal is one of the regions whose capacity to self-finance governance, development, and public services is still reliant on transfers from the central and provincial governments. This is evident in the low Regional Financial Independence Ratio, which stands at 22.10%. Kabupaten Tegal has yet to fully implement fiscal decentralization, as indicated by the fluctuating fiscal decentralization ratio, which falls into the low category. To provide better public services, Kabupaten Tegal must optimize its Local Own-Source Revenue (PAD) potential.